Pengaruh Budaya Mandailing Natal Terhadap Remaja Di Desa Parbangunan dalam moderasi beragama dimasa Pandemi Covid-19 - Kasmir _ Sim; Saudin Hamdani; Fauziah Nur; Henri Lubis (PKM-P, 2021)
ABSTRACT Culture is an abstract form of the habits that exist in a society. Indonesia is a country with a lot of cultural wealth, one of which is the Mandailing Natal culture. This study focuses on the influence of Mandailing Natal culture on one of the villages in Mandailing Natal, namely the village of Parbangun whose research object is teenagers in religious moderation during the COVID-19 pandemic. Quantitative and field studies are the methods used in this research, namely by collecting sources of journals and books and then observing the data directly observed in the village of Parbangunan. keywords; Culture, Religious Moderation, Covid-19 Pandemic